Studies in Medieval Legal Thought : Public Law and the State 1100-1322 - Post, Gaines, 1902-1987 (Book collections on Project MUSE., 1964)
This volume brings together eleven articles by a distinguished medieval scholar. The major emphasis is on legal thought that resulted from the revival of Roman law at Bologna and on the influence this thought had on medieval "constitutionalism." Includes such important studies as "A Romano-Canonical Maxim, Quod Omnes Tangit, in Bracton," and "Status Regis and Lestat du Roi in the Statute of York."Originally published in 1964.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.